ADDRESSING AEC 2016 BY ANALYZING THE SERVICE QUALITY OF SILOAM HOSPITAL MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS (IPA) - Tumiwa, Johan; Paruntu, Carolus P. (Journal of Asean Studies on Maritime Issues, 2016)
Entering the Asean Economic Community (AEC), competition in all sectors, including the health care industry, increasingly tight. Therefore, the hospital needs to improve the quality and competence of human resources to face the era of openness. The role of the hospital is very big also need to beÂ  kept synergy between public and private hospitals owned by the government even needs to be improved. MEA is important moment for the entire hospital either private or government synergy. Synergies that by taking part in the National Health Insurance program (JKN) managed BPJS. Especially targeted in 2019, Indonesia will achieve universal health coverage, or universal health insurance, in which the entire people of Indonesia covered with JKN. In the face of MEA private hospitals began to increase the competence of human resources, ranging from doctors, nurses, and midwives. Improving the competence of this is done through ongoing training. The objective which this thesis intends to achieve is to analyze the service quality of Siloam Hospital Manado by using Importance Performance Analysis (IPA).The sample taken is using simple random sampling of 100 people who experience the service of Siloam Hospital Manado.